2015
DOI: 10.1074/jbc.m115.639237
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Liver Kinase B1 (LKB1) in Beta Cells Enhances Glucose-stimulated Insulin Secretion Despite Profound Mitochondrial Defects

Abstract: Background: LKB1 regulates multiple aspects of pancreatic β cell biology.Results: LKB1 loss in β cells leads to profound mitochondrial defects yet increases glucose-stimulated insulin secretion in a mitochondria-independent mechanism.Conclusion: LKB1 is essential for mitochondrial maintenance and negatively regulates a distal step of insulin secretion.Significance: LKB1 loss exposes powerful mechanisms of insulin secretion that can override defects in the classic triggering pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 70 publications
3
43
0
Order By: Relevance
“…ADP cellular content, which was much higher at basal glucose concentration in metformin-treated cells, reached control values in the presence of stimulatory glucose concentrations; this in turn alters the ATP/ADP ratio that is permissive for K ATP channel closure and enhanced insulin secretion (2), satisfying the set criteria for ADP and the ATP/ADP ratio as candidate MCFs. Considering that Mg 2ϩ -bound ADP activates K ATP channels and prevents ␤-cell depolarization and insulin exocytosis (46), the present data favor the view that ADP acts as an "off" signal and is functionally more relevant for insulin release than ATP (33,(47)(48)(49)(50), at least in the second phase of GIIS.…”
Section: Metabolic Signaling Of Glucose For Insulin Secretionsupporting
confidence: 65%
“…ADP cellular content, which was much higher at basal glucose concentration in metformin-treated cells, reached control values in the presence of stimulatory glucose concentrations; this in turn alters the ATP/ADP ratio that is permissive for K ATP channel closure and enhanced insulin secretion (2), satisfying the set criteria for ADP and the ATP/ADP ratio as candidate MCFs. Considering that Mg 2ϩ -bound ADP activates K ATP channels and prevents ␤-cell depolarization and insulin exocytosis (46), the present data favor the view that ADP acts as an "off" signal and is functionally more relevant for insulin release than ATP (33,(47)(48)(49)(50), at least in the second phase of GIIS.…”
Section: Metabolic Signaling Of Glucose For Insulin Secretionsupporting
confidence: 65%
“…Correspondingly, recently published transcriptomic data [52], [53] also demonstrate detectable, although low, levels of Elovl2 mRNA in adult human β cells. Interestingly, Elovl2 expression was also up-regulated ∼2-fold in mouse islets in response to deletion of the tumor promoter Liver Kinase B1 (LKB1) [54], a condition in which glucose-stimulated insulin secretion is also enhanced [55]. Interestingly, we also found that over-expression of Elovl2 in β cells potentiated glucose-induced insulin secretion and was associated with an increase of DHA levels.…”
Section: Discussionmentioning
confidence: 60%
“…Skeletal muscle-specific deletion of Lkb1 regulates muscle development, lipid oxidation, glucose homeostasis, and insulin sensitivity13141516. In addition, tissue-specific deletions of Lkb1 in adipose tissue1718, pancreas192021 and brain2223 further demonstrate that Lkb1 plays important roles in these tissues. Moreover, loss of Lkb1 regulates haematopoietic stem cells’ metabolism and survival345, muscle stem cells’ proliferation and differentiation1624, and pancreatic β cells’ polarity20.…”
mentioning
confidence: 98%